Pengaruh Pengembangan Karir dan Komunikasi Organisasi Terhadap Kinerja Anggota TNI AU Pangkalan Wiriadinata Tasikmalaya - Destia Agrisna Utami; Suci Putri Lestari; Titin Patimah (Journal of Management and Creative Business, 2023)
This study aims to determine the effect of career development and communication organization on the performance of members of the Indonesian Air Force Base Wiriadinata. The method used is a case study, data obtained through questionnaires to members of the Indonesian Air Force Base Wiriadinata. Withdrawal of samples using random sampling technique, using the Slovin formula and the method of analysis used is the method of multiple linear regression analysis. The results of the research show that career development, organizational communication and performance are included in the Very Good classification. Simultaneously career development and organizational communication have a significant effect on the performance of members of the Indonesian Air Force Base Wiriadinata. Partially, career development and organizational communication variables have a significant effect on the performance of members of the Indonesian Air Force Base Wiriadinata.